Pollinators diversity and their effects on rapeseed (Brassica campestris L. var. toria) production and productivity in Chitwan, Nepal - Rijal, Shiva P.; Thapa, Resam B.; Sharma, Moha D.; Sah, Shrawan K.; GC, Yubak Dhoj (Journal of Agriculture and Environment, 2018)
Crop pollination is crucial for increasing yield, ensuring food security and improving livelihoods. To quantify the response of pollinators on rapeseed, an experiment was conducted in randomized complete block design (RCBD) at three agro-ecological sites: Semi-natural (Megauli), organic (Fulbari) and intensive agriculture (Jutpani) Village Development Committees of Chitwan district in 2012/013 and 20013/014. The treatments were: i) open pollination; ii) plants caged with honeybees (Apis melifera L.); iii) hand pollination; and iv) control (plots caged without pollinators) replicated four times. Pollinators visiting rapeseed flowers, plant height, branch number, siliqua/plant, pods weight/ siliqua, test weight, and seed yield/hectare were recorded. The dominant pollinators were Hymenopterans mostly honeybees. The impact of pollinators on each system resulted in significantly increased yield attributes compared to no-pollination, which clearly indicates the need of integrating managed pollination and pollinators' conservation to sustain rapeseed production in Chitwan through biodiversity-based ecosystem services.